Electrophysiological characteristics in adolescents with non-suicidal self-injury: an event-related potential study and source analysis - Yoon, Sung-Hoon; Kim, Ji Sun; Lee, Hyeon-Ah; Lee, Woo-Seung; Song, Young Wook; Shim, Se-Hoon (Frontiers in Psychiatry, 2025)
IntroductionNon-suicidal self-injury (NSSI) is a serious concern in adolescents and is associated with impairments in impulsivity and social functioning. However, the underlying neural mechanisms remain unclear. This study aimed to examine inhibitory control and its association with depressive symptoms and interpersonal distress in adolescents with NSSI using event-related potentials (ERPs) and source-level analysis.MethodsA total of 51 adolescents with NSSI and 50 HC were recruited. Psychological characteristics were assessed using standardized scales including the Interpersonal Needs Questionnaire (INQ) and Short UPPS-P Impulsivity Scale (SUPPS-P). EEG were recorded during a go/no-go task to measure P3 amplitudes. Source analysis was performed to localize the neural activity. Group differences were analyzed using RMANOVA, followed by Pearson correlation and mediation analyses to evaluate the relationships among the variables.ResultsThe NSSI group showed significantly lower accuracy than HCs. The interaction between group and electrode site was significant (p = .032, ηp² = .010), indicating spatially specific reductions in no-go P3 amplitude in the NSSI group. No-go P3 at Fz was negatively correlated with depressive symptoms and interpersonal distress. Source-level analysis revealed marginally reduced activation in the right superior frontal gyrus in the NSSI group but diminished after adjusting for depressive symptoms. Mediation analysis indicated that depressive symptoms significantly mediated the relationship between both neural indices and interpersonal distress.ConclusionsAdolescents with NSSI exhibit impaired inhibitory control that is associated with depressive symptoms and social distress. These findings highlight the role of affective dysregulation in linking cognitive control deficits to interpersonal functioning in NSSI.